Permainan Ladder and Snakes untuk latihan kekuatan - Muzdalifah, Erliyan; Taufik, Mr (Universitas Negeri Malang, 2020)
Abstract: The purpose of this study is to develop a ladders and snakes training game that can be used for strength training for athletes PPLM Volleyball, State University of Malang. This research and development uses the ADDIE R&D method which consists of five stages, namely analysis, design, development, implementation or testing, and evaluation. Data collection was carried out using questionnaire sheets obtained from expert validation and product trials on athletes. The data analysis technique used as a reference is descriptive percentages, from the sum of the results of the analysis using a Likert scale. The product was validated by 2 experts with the following percentage results, expert in volleyball sports at 83.3%, sports training experts at 88.8%. Product trial subjects are 14 athletes PPLM Volleyball, State University of Malang with the measured aspects of ease, clarity, attractiveness and pleasure with an average yield of 95.6% (very good). From the data obtained it can be concluded that the development of the ladders and snakes training game can be accepted and used for strength training for athletes PPLM Volleyball State University of Malang Keywords: Games, Volleyball, Strenght Training Abstrak: Tujuan dari penelitian ini adalah mengembangkan permainan ladders and snakes training yang bisa digunakan untuk latihan kekuatan pada atlet PPLM Bolavoli Universitas Negeri Malang . Penelitian dan pengembangan ini menggunakan metode R&D model ADDIE yang terdiri dari lima tahapan, yaitu analisis, desain, pengembangan, implementasi atau uji coba, dan evaluasi. Pengumpulan data dilakukuan dengan menggunakan lembar kuesioner yang diperoleh dari validasi ahli dan uji coba produk pada atlet. Teknik data analisis yang dipakai sebagi acuan adalah deskriptif persentase, dari hasil penjumlahan hasil analisis mengunakan skala likert. Produk divalidasi oleh 2 ahli dengan hasil persentase sebagai berikut, ahli cabang olahraga bolavoli sebesar 83,3%, ahli kepelatihan olahraga sebesar 88,8%. Subjek uji coba produk yaitu 14 atlet PPLM Bolavoli Universitas Negeri Malang dengan aspek yang diukur yaitu kemudahan, kejelasan, kemenarikan dan kesenangan dengan hasil rata-rata persentase 95,6% (sangat baik). Dari data yang didapat dapat disimpulkan bahwa pengembangan permainan ladders and snakes training ini dapat diterima dan digunakan untuk latihan kekuatan pada atlet PPLM Bolavoli Universitas Negeri Malang. Kata kunci: Permainan, bolavoli, latihan kekuatan